Business Communication Strategy of Tanah Abang Traders Facing the Flow of Live Streaming Commerce (LSC) - Alexandrina, Elke; Ramonita, Latifa; Wempi, JA (GoAcademica Research & Publishing, 2024)
Tanah Abang, as one of the largest shopping malls in Indonesia, is facing significant changes in consumer behavior, which is increasingly turning from traditional buying to live-streaming commerce platforms. This research is intended to explore and analyze the business communication strategies implemented by merchants in Tanah Abang in response to the growing trend of live-streaming commerce (LSC). This research uses a case study approach to traders in Tanah Abang and analyzes how they adjust their business communication strategies in line with technological developments and the live-streaming commerce phenomenon. This research methodology uses a descriptive qualitative design, with data collection through in-depth interviews with traders, direct observation at the trading location, and content analysis presented by traders on social media. The results of this study provide valuable insights into business communication strategies suitable for live-streaming commerce, including the use of social media, product promotion, customer interaction, and other tactics. The findings of this study have important implications for merchants in Tanah Abang and similar businesses in various countries that are facing changes in the world of commerce due to the impact of technology and changes in consumer behavior. In addition, this study contributes to the literature on business communication strategies in the context of e-commerce and the rapidly growing live-streaming commerce.